Larangan Maisr dalam Al-Quran dan Relevansinya dengan Perekonomian - Hilyatin, Dewi Laela (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2021)
Gambling (maisÃ„Â«r) is strictly prohibited by the Qur'an. However, in reality, the practice of gambling has always existed from time to time, even from its simple form to its complex form. The prohibition of gambling in the Qur'an is stated in three verses: Al BÃ„Âqarah: 219, Al MÃ„Âidah: 90 - 91. Of the three verses, it is explained that gambling (maisÃ„Â«r) benefits humans, but the harm is much greater. This is very relevant from the economic point of view. Gambling does not increase economic growth, because it does not produce output, what only happens is the movement of money and goods between individuals. Gambling also does not increase productivity, there is only a waste of energy and time, even gambling can be called a killing time. In the context of the state, the activity of gambling in the aggregate greatly reduces national income, not the opposite.